Diabetes and Arrhythmias: Pathophysiology, Mechanisms and Therapeutic Outcomes - Grisanti, Laurel A. (Frontiers in Physiology, 2018)
The prevalence of diabetes is rapidly increasing and closely associated with cardiovascular morbidity and mortality. While the major cardiovascular complication associated with diabetes is coronary artery disease, it is becoming increasingly apparently that diabetes impacts the electrical conduction system in the heart, resulting in atrial fibrillation and ventricular arrhythmias. The relationship between diabetes and arrhythmias is complex and multifactorial including autonomic dysfunction, atrial and ventricular remodeling and molecular alterations. This review will provide a comprehensive overview of the link between diabetes and arrhythmias with insight into the common molecular mechanisms, structural alterations and therapeutic outcomes.